The role of natural killer cells, gamma delta T-cells and other innate immune cells in spondyloarthritis - Al-Mossawi, M; Ridley, A; Kiedel, S; Bowness, P (2013)
PURPOSE OF REVIEW: Natural killer (NK) cells, gamma delta (γδ) T-cells and other innate immune cells are important lymphocyte subsets able both to produce cytokines including the pro-inflammatory cytokine IL-17 and to kill cellular targets. This review describes the features of NK cells, γδ T-cells and other innate immune cells, and outlines the evidence for their potential pathogenic roles in spondyloarthritis (SpA). RECENT FINDINGS: NK cells and T cells both express receptors that recognize aberrantly folded human leucocyte antigen. This interaction seems to polarize towards a type 17 immunity programme which has been increasingly implicated in SpA pathology. γδ T-cells have also been shown to be polarized towards a type 17 immunity programme in SpA. Gut interactions with the microbiome can influence NK and innate lymphoid immune responses in SpA and other related diseases. A newly identified population of resident lymphoid cells at the enthesis for the first time offers an explanation for the anatomical localization of SpA. SUMMARY: NK cells, γδ T-cells and other innate immune cells are capable of sharing expression of both transcription factors, including RORγt, and cell surface receptors, such as the killer immunoglobulin-like receptors. There is increasing genetic and functional evidence that they contribute to the RORγt-driven inflammatory type 17 immune responses, and they may link gut inflammation and joint pathology in SpA. © 2013 Wolters Kluwer Health / Lippincott Williams and Wilkins.